Tourist itineraries and its role in developing eco-tourism(A case study of Lattakia Governorate ) (Damascus University Journal of arts and humanities sciences, 2025)
Tourism industry requires a new way to deal with the place based on adapting new concepts discovered by understanding the place data ( material and immaterial )including distinguishing it from traditional ways of tourism to make that industry an essential motivation in economic development. Under the changeable and contradictable tourist markets, there is no insurance to have success in this industry unless continuous invention are achieved which support the continuity of the tourist resources expanding its production and decreasing the load no the environment. From here comes the importance of focusing on supporting and developing eco-tourism that encourages the continuous useage of natural and cultural resources. Theimportance of this research coms from the importance of Lattakia governorate with in the geographical tourist system in Syria because its natural and human factors border a promising geographical space. Developing eco-tourism requires showing the tourist the natural and cultural product properly, the promoting this product to increase tourist traffic. The most important thing in this study is to show the role of tourist itineraries in promoting and supporting eco-tourism because it works to join environmental tourist regions together, the thing that helps to direct tourist towards distinguished environmental region to know it. Depending on the results, the existence of tourist itineraries in the eco-tourism plan has a positive advantage on natural and cultural environment and contributes in the diversity of tourist products which provides jobs for people in local community and achieves tourist development which benefits the national economy.
Keywords: Eco-Tourism; Itineraries; Lattakia Governorate; Tourism